Modeling current and future groundwater demands in the White Volta River Basin of Ghana under climate change and socio-economic scenarios - Mensah, J. K.; Ofosu, Eric Antwi; Akpoti, Komlavi; Kabo-Bah, A. T.; Okyereh, S. A.; Yidana, S. M. (Elsevier, 2022)
Study region: White Volta River Basin, Ghana. Study focus: Groundwater sustainability is becoming a major concern in the face of population growth, land use land cover (LULC), and climate changes. The Water Evaluation and Planning (WEAP) model is used in this study to analyse the current and future groundwater demands for the period of 2015–2070. Two Representative Concentration Pathways (RCP4.5 and RCP 8.5) scenarios from statistically downscaled fifteen CMIP5 models were combined three Shared Socioeconomic Pathways (SSPs 2,3 and 5) scenarios in the nine sub-catchments of the White Volta River Basin. New hydrological insights for the study region: The WEAP model was calibrated (2006–2012) and validated (2013–2020) using streamflow data from six gauges in five sub-catchments. The findings show that climatic change and socio-economic development will result in a disparity between groundwater supply and demand in sub-catchments with greater socioeconomic growth, especially those with higher population density and arable agricultural land. Among the basin’s nine sub-catchments, four will experience water scarcity under all future scenarios. While the groundwater flow and recharge data may be evaluated using several physical hydrological models, the calibration and validation results suggest that the current modeling approach is capable of reliably predicting future groundwater demand with associated uncertainties. The study establishes a link between climate change, socio-economic growth, and groundwater availability in the White Volta River Basin.